Creating National Champions in France: A Little Less Égalité, a Little More Sélectivité? - Highman, Ludovic (International Higher Education, 2018)
The merger between Paris–Sorbonne University (Paris IV) and Pierre and Marie Curie University (Paris VI) will create a single, multidisciplinary institution in the heart of Paris. This merger needs to be contextualized within the national and European contexts, in order to shed light on the drivers, opportunities, and challenges behind a trend that has become increasingly visible among European nations, which seek to rationalize and consolidate their higher education systems.